Removal of pentachlorophenol from contaminated wastewater using phytoremediation and bioaugmentation processes - Werheni Ammeri, Rim (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
The phytoremediation procedure was conducted by Lemna gibba (L) and Typha angustifolia (T) and the bioaugmentation procedure used P. putida HM627618. The ability of the selected P. putida HM627618 to tolerate and remove PCP (200 mg L-1) was measured by high performance liquid chromatography analysis and optical density at 600 nm. Five different experiments were conducted in secondary treated wastewater for PCP testing removal (100 mg L-1) including two phytoremediation assays (T + PCP; L + PCP), three bioaugmentation-phytoremediation assays (T + B + PCP; L + B + PCP; L + T + B + PCP) and a negative control assay with PCP. Various analytical parameters were determined in this study such as bacterial count, chlorophylls a and b, COD, pH and PCP content. The main results showed that the average PCP removal by P. putida HM627618 was around 87.5% after 7 days of incubation, and 88% of PCP removal was achieved by treatment (T + B) after 9 days. During these experiments, pH, COD and chloride content showed a net increase in all treatments. The chlorophylls a and b in case of (T) and (L) Chlorophylls a and b for T and L phytoremediation showed a decrease with a value less than 10 μg/mg of fresh material after 20 days of cultivation